Feasibility study of seaweed (Gracilaria firma) powder as salt substitute - Targa, Roxanne Mae V.; Francisco, Ma. Leonora dL. (c2011.)
ABSTRACT Consumption of sodium from food products, more than the recommended intake, has resulted in the prevalence of cardiovascular diseases. This promotes the use of salt substitutes to reduce sodium intake. The objective of this study was to develop a salt substitute from seaweed (Gracilaria firma) powder by determining the seaweed's drying parameter; assessing the physico-chemical and sensorial qualities of the seaweed powder; and estimating its optimum exchange rate with salt in two food systems (fish soup and fishball). The statistical analyses used were mean, standard deviation, Chi-square analysis, Analysis of Variance, and Least Significant Difference. The drying time for the seaweed with moisture content (wet basis)of 85.8% was at least 40 min at 65°C in Sandvik convective dryer and the drying rate curve was cuvilinear. The seaweed powder had a pH of 6.03, Aw of 0.342, moisture content (dry basis) of 7.98%, green to grayish green in color, and salt content of 9.484%. The seaweed stock (0.75% w/v) was rated as 'dislike slightly' in terms of overall saltiness. Its saltiness was equivalent to the salt solution containing the same amount of sodium chloride. Analysis of Variance results at P<0.05 showed significant differences in all of the sensorial attributes for the two food systems except for umami and fish intensity in fish soup. A salt reduction of 17.3% and 17.7% for fish soup and fishball, respectively was obtained. Presence of high glutamic acid in seaweeds could have a synergistic effect with salt which maintained the saltiness even if the salt content was reduced. However, seaweed powder could only be used as salt substitute at lower concentrations due to its off-odor and extraction of agar with acids. Reductionof the off-odor of the seaweed powder could improve its potential as salt substitute.
Thesis(BSFT)--University of the Philippines Diliman.
Keywords: Marine algae; Marine algae as food